PARTISIPASI LMDH WONO LESTARI DALAM PROGRAM PENGELOLAAN HUTAN BERSAMA MASYARAKAT DI RPH SUMBEREJO BKPH NGLAWUNGAN KPH BLORA - , DWI MUTIARA AYU, Bowo Dwi Siswoko S.Hut., M.A ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Community Jointly Forest Management Program (PHBM) was determined in the Decree of Supervision Board of Perum Perhutani Number 136/KPTS/DIR/2001 to deliver a forest resources management direction by combining economics, ecological and social aspects proportionally. The PHBM enforcement by establishing a non-govermental organization but village based that was called LMDH. To know how far the PHBM enforcement succsess one of them could be seen from LMDH participation. This research was aimed to know an institutional profile, activities and participation of LMDH Wono Lestari in PHBM enforencement and also to know problems facing in that institution. The research used a survey method. Data taking technique was through an interview an questionnaire. This research was located in RPH Sumberejo, BKPH Nlawungan, KPH Blora. From the research, it could be known that activities performed by LMDH Wono Lestari in running PHBM programs were among others to manage administration in each PHBM activities, hold a meeting each month and managing sharing fund for PHBM activivities or for productive business. The participation of LMDH Wono Lestari in a PHBM based forest management in Sumberejo Village Head implementation, results, monitoring an evaluation. Problems facing was that LMDH and community had not fully understood on PHBM due to socialization officers on PHBM from Perhutani was not in their field so that the information objective given was not achieved.